ANOMALOUS HALL-EFFECT FROM VORTEX MOTION IN HIGH-TC SUPERCONDUCTORS - CHEN, JL; YANG, TJ (My University, 1994)
In this work, the unusual Seebeck effect is taken into consideration in explaining the possible origin of the anomalous Hall effect for high-T(c) superconductors. Combining Maki's theory of transport entropy and Tinkham's theory of resistive transition, we explain why the anomalous Hall effect can be observed in high-T(c) superconductors, but is absent in most conventional superconductors. The behavior of rho(xy) (H, T) in our theory is qualitatively consistent with experiments. In addition, our theory not only predicts that rho(xy) will become positive from rho(xy) < 0 when the temperature is decreased in constant magnetic field, but also predicts that \rho(xy)\ is-proportional-to rho(xx)2 in the region of pho(xy) < 0 and that the negative p(xy) will diminish with increasing defect concentration.